Microbiota Modulation of the Gut-Lung Axis in COVID-19 - de Oliveira, Gislane Lelis Vilela; Oliveira, Camilla Narjara Simão; Pinzan, Camila Figueiredo; de Salis, Larissa Vedovato Vilela; Cardoso, Cristina Ribeiro de Barros (Frontiers in Immunology, 2021)
COVID-19 is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), and according to the World Health Organization (WHO), to date, SARS-CoV-2 has already infected more than 91.8 million people worldwide with 1,986,871 deaths. This virus affects mainly the respiratory system, but the gastrointestinal tract (GIT) is also a target, meanwhile SARS-CoV-2 was already detected in oesophagus, stomach, duodenum, rectum, and in fecal samples from COVID-19 patients. Prolonged GIT manifestations in COVID-19, mainly the diarrhea, were correlated with decreased richness and diversity of the gut microbiota, immune deregulation and delayed SARS-CoV-2 clearance. So, the bidirectional interactions between the respiratory mucosa and the gut microbiota, known as gut-lung axis, are supposed to be involved in the healthy or pathologic immune responses to SARS-CoV-2. In accordance, the intestinal dysbiosis is associated with increased mortality in other respiratory infections, due to an exacerbated inflammation and decreased regulatory or anti-inflammatory mechanisms in the lungs and in the gut, pointing to this important relationship between both mucosal compartments. Therefore, since the mucous membranes from the respiratory and gastrointestinal tracts are affected, in addition to dysbiosis and inflammation, it is plausible to assume that adjunctive therapies based on the modulation of the gut microbiota and re-establishment of eubiosis conditions could be an important therapeutic approach for constraining the harmful consequences of COVID-19. Then, in this review, we summarized studies showing the persistence of SARS-CoV-2 in the gastrointestinal system and the related digestive COVID-19 manifestations, in addition to the literature demonstrating nasopharyngeal, pulmonary and intestinal dysbiosis in COVID-19 patients. Lastly, we showed the potential beneficial role of probiotic administration in other respiratory infections, and discuss the possible role of probiotics as an adjunctive therapy in SARS-CoV-2 infection.